Meaning and interpretation of music in cinema - Neumeyer, David; Buhler, James (Musical meaning and interpretation, 2015)
By exploring the relationship between music and the moving image in film narrative, David Neumeyer shows that film music is not conceptually separate from sound or dialogue, but that all three are manipulated and continually interact in the larger acoustical world of the sound track. In a medium in which the image has traditionally trumped sound, Neumeyer turns our attention to the voice as the mechanism through which narrative (dialog, speech) and sound (sound effects, music) come together. Complemented by music examples, illustrations, and contributions by James Buhler, Meaning and Interpret
Keywords: Motion picture music : Analysis, appreciation; Motion picture music : History and criticism